Teknik Permainan Hasapi Pada Lagu Buku Ende No. 585.’’Somba Ma Jahowa” Dalam Ibadah Minggu Di Gereja HKBP Bahal Batu I” - Handoco Rumahorbo; Robert KA. Simangunsong; Roy JM. Hutagalung; Boho P. Pardede; Aprinaldi Simarangkir (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research examines the technique of playing hasapi to accompany the song Buku Ende No. 585.Somba Ma Jahowa Debata. Through a literature study approach and direct observation, this thesis presents various basic and advanced techniques used by hasapi players. First, this thesis describes how to hold and pluck hasapi strings, as well as basic techniques for producing clear and resonant sound. Next, it discusses the use of melodic and rhythmic variations in playing hasapi, including ornamentation and improvisation techniques which are generally used in traditional Batak music performances. This research also outlines the important role of learning and knowledge in the hasapi playing community. The results of this research show that a deep understanding of hasapi playing techniques requires consistent practice and a deep understanding of the cultural context. Apart from that, this thesis concludes that the development of hasapi playing techniques not only enriches Batak cultural heritage, but is for the glory of God.